The Relationship between Self-Concept and Communication Anxiety in Students: A Quantitative Approach - Hasanah, Uswatun (Universitas Islam Negeri Sumatera Utara, 2025)
This study measures the relationship between self-concept and communication anxiety in students by collecting research to find the results of problems that exist on campus and the current campus environment. The primary approach in this research is quantitative. The data to be processed quantitatively in this study comes from a questionnaire. The questionnaire method is divided into a subject identity checklist, the Tennessee Self-Concept Scale, and a communication anxiety scale. A sample of 100 students was drawn based on non-randomly selected majors at Pancasila University: Economics, Law, Psychology, Communication, and Pharmacy. Twenty students were selected from each major. The sampling technique used non-probability sampling, namely the side quota technique. There was no significant relationship between self-concept and communication anxiety in students. The results showed an r value of 0.094, which is not significant at α = 0.05. This means there is no correlation between self-concept and communication anxiety. Thus, the null hypothesis (H0) is accepted.